Teachers' Social Representations in Relation to EJA: affectivity and teacher training - Poliana da Silva Almeida Santos Camargo (Universidade Federal do Rio Grande do Sul, 2017)
The aim of this article is to present Youth and Adult Education - EJA teachers' social representations, concerning their teacher training and affectivity in the teaching-learning process. The participants were teachers who work at the Youth and Adult Education Center - CEJA and the Youth and Adult Education State Center - CEEJA. Data were collected using the Words Free Association Test (TALP) and interviews. We can infer that the teachers' social representations are actualized in their daily practice through their commitment with the students, and are based on the affective perspective, in which love and responsibility are more significant than technical competence, teaching practice and pedagogical training.